2005
DOI: 10.1097/01.ajp.0000146166.15529.8b
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Distress in Children With Cancer

Abstract: Self-report measures, behavioral indicators, and physiological changes are not interchangeable outcomes. Treatment strategies were effective for minimizing subjective and behavioral distress, but not necessarily for physiological reactions. Future research should focus on individual differences in these responses, and treatment outcome studies aimed at reducing distress must be clear about the specific goals of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Acute pain has been found to elicit HPA arousal (e.g., Dixon et al 2004). However, children can show cortisol elevations to invasive procedures even in the absence of observable or reported discomfort (Walco et al 2005), and increased cortisol levels after venipuncture have been found to be more attributable to emotional than physical factors (Hubert et al 1989). Furthermore, it is likely that the topical analgesia administered to boys in this study minimized the extent to which actual pain was experienced or contributed to stress responses.…”
Section: Discussionmentioning
confidence: 83%
“…Acute pain has been found to elicit HPA arousal (e.g., Dixon et al 2004). However, children can show cortisol elevations to invasive procedures even in the absence of observable or reported discomfort (Walco et al 2005), and increased cortisol levels after venipuncture have been found to be more attributable to emotional than physical factors (Hubert et al 1989). Furthermore, it is likely that the topical analgesia administered to boys in this study minimized the extent to which actual pain was experienced or contributed to stress responses.…”
Section: Discussionmentioning
confidence: 83%
“…Children's Pain assessment can be conducted by three means: selfevaluating, selfless-evaluating by behaviour observation and recording, Physiological measurements [1]. However, according to some scientists; the ideal evaluation is the combined evaluation which includes self-evaluating for pain associated with one of the methods stated above [2], but this approach can be considered unpractical, inapplicable and useless for children in the phase before talking or whom are unable to talk, or those have perceptual problems, so some of scientists said that it is better to evaluate pain by selfless methods that depends on watching Child's reaction against pain alarm and registering it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Acute pain may be taken to include all painful experiences lasting for less than 3 months duration [1]. A thorough acute pain assessment should be conducted within a broader social and developmental perspective, considering information from various sources, which may include self-reported information, behavioral observations, physiological measures, parent-or clinician-reported information, and the patient's medical history [2], complemented by an understanding of pain mechanisms and pathophysiology [3]. Each of these assessment modalities may provide valuable information about the pain experience.…”
Section: Introductionmentioning
confidence: 99%